2023
DOI: 10.3390/su15086938
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Digital Technology Innovation Network Embedding on Firms’ Innovation Performance: The Role of Knowledge Acquisition and Digital Transformation

Abstract: In the digital economy context, enterprises’ competitive environment is changing rapidly. Historically, enterprises rely on a solitary fight to occupy the market. Now, enterprises should actively embed into digital technology innovation networks to maximize access to external digital technology knowledge resources through organizational cooperation and achieve the absorption of digital resources and technologies. However, the relationship between digital technology innovation network embedding and innovation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Gao et al (2023) carried out analysis and research from the perspective of government support and stakeholders, and found that government subsidies, as an intermediary, affect the digitization level of enterprises and thus affect the GI of enterprises, and the fulfillment of corporate social responsibility also has a positive impact on GI [42]. Ge et al (2023) conducted a study on the correlation between digital technology innovation network embedding and enterprise innovation performance, and the results showed that knowledge acquisition intermediary network embedding played an intermediary role in digital technology innovation performance, proving that digital technology and enterprise performance have a positive influence relationship [43]. Dong et al (2023) conducted a static and dynamic empirical study on the integrated construction supply chain (IBSC) of construction enterprises, and the results showed that the digital integration degree of IBSC and the green knowledge collaboration ability between enterprises are conducive to improving the DGI performance of enterprises [44].…”
Section: Factors Related To Dgi Performancementioning
confidence: 99%
“…Gao et al (2023) carried out analysis and research from the perspective of government support and stakeholders, and found that government subsidies, as an intermediary, affect the digitization level of enterprises and thus affect the GI of enterprises, and the fulfillment of corporate social responsibility also has a positive impact on GI [42]. Ge et al (2023) conducted a study on the correlation between digital technology innovation network embedding and enterprise innovation performance, and the results showed that knowledge acquisition intermediary network embedding played an intermediary role in digital technology innovation performance, proving that digital technology and enterprise performance have a positive influence relationship [43]. Dong et al (2023) conducted a static and dynamic empirical study on the integrated construction supply chain (IBSC) of construction enterprises, and the results showed that the digital integration degree of IBSC and the green knowledge collaboration ability between enterprises are conducive to improving the DGI performance of enterprises [44].…”
Section: Factors Related To Dgi Performancementioning
confidence: 99%
“…The network embedding is a continuous social relationship situation showed by enterprises in economic activities. The impact of network embedding on the performance and market competition advantages of enterprises has been generally recognized by the academic community (Chen et al, 2023;Cui et al, 2017;Ge et al, 2023). Different forms and performances embedded in the network will lead to differences in enterprise performance and competitive advantages, that is, the different positions and structures embedded in the network in the network will show differences in the performance level of enterprises (Liu, 2009).…”
Section: The Impact Of Network Embedding On Enterprise Performancementioning
confidence: 99%
“…This information is used to measure the dimensions of digital technology applications in subsequent analysis. For the definition of digital technology, this paper processes data according to the definition in the "Reference Relationship Table of the Core Industry Classification of the Digital Economy and the International Patent Classification (2023)" issued by China National Intellectual Property Administration [67,68]. We follow the degree centrality measurement mentioned in existing work [69] to calculate network centrality metrics in structure and relational embeddings.…”
Section: Sample Selection and Data Sourcesmentioning
confidence: 99%